Shear strengthening of reinforced concrete beams with Hybrid Composite Plates (HCP) technique: Experimental research and analytical model. (15th October 2016) - Baghi, Hadi; Barros, Joaquim A.O.; Menkulasi, Fatmir
Highlights: RC beams shear strengthened with HCPs were tested under monotonic load. The influence of CFRP laminate inclination and ratio was studied. Mechanical anchors avoided premature detachment of the HCPs. The beams strengthened with HCPs show improvement in terms of load carrying capacity. The proposed analytical model predicts the shear strength of RC beams strengthened with HCPs with good accuracy. Abstract: This paper presents a study on the efficiency of Hybrid Composite Plates (HCPs) in enhancing the shear strength and stiffness of reinforced concrete (RC) beams. HCP is a thin plate of Strain Hardening Cementitious Composite (SHCC) reinforced with Carbon Fiber Reinforced Polymer (CFRP) laminates applied to the sides of reinforced concrete beams according to the Near Surface Mounted technique (NSM). Due to the excellent bond conditions between SHCC and CFRP laminates, these reinforcements provide the necessary tensile strength capacity to the HCP. To examine the efficiency of HCPs as a shear strengthening technique, a total of 17 RC beams are tested. Seven of these beams have a rectangular cross-section and ten have a T cross-section. The influence of the percentage and inclination of the CFRP laminates on the shear strengthening effectiveness of HCPs is investigated. Two different processes for applying the HCPs to the beams' concrete substrate are examined: (1) using epoxy adhesive; and (2) using mechanical anchors in addition to the epoxy adhesive. It is demonstrated that when only epoxy adhesive is used, the shear strengthening contribution of the HCPs is limited by the tensile strength of the concrete substrate of the strengthened beams. When mechanical anchors are applied in addition to the epoxy adhesive, the shear strengthening potential of HCPs is fully mobilized. An analytical model is proposed to predict the shear strength of RC beams strengthened with HCPs. It is demonstrated that the analytical model predicts with good accuracy the shear strength of RC beams strengthened with HCPs.